Information Technology Role on Private Commercial Banks Efficiency with Cost and Profit DEA Technology - Md. Azizul Baten (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
IT plays a pivotal role to improve the competitiveness of the bank by providing its existing customers with satisfactory services, while at the same time bringing about a significant reduction in cost. This study measures the effect of IT factors on cost and profit efficiency of Private Commercial Banks (PCBs) in Bangladesh employing cost and profit Data Envelopment Analysis (DEA) and Ordinary Least Square (OLS) method. The average cost efficiency (41.4%) was recorded higher than the average profit efficiency (18.8%) for PCBs. Prime bank was the most cost and profit efficient among PCBs. The Credit card transaction (0.000006) and Credit card expenses (0.0002) were observed positively significant for cost efficiency of PCBs and the IT personnel expenses (0.0015) and Credit card transaction (0.00008) were positively significant for profit efficiency of PCBs. IT factors were found more significant for PCBs in profit efficiency. The results attained from this study could aid government, managers and depositors to remove the hindrance of progress in Bangladesh. This type of empirical analysis could be applied in another sector of the economic market.